Quantification of cardiovascular disease biomarkers via functionalized magnetic beads and on-demand detachable quantum dots - Park, Hoyoung; Lee, Jong-Wook; Hwang, Mintai P.; Lee, Kwan Hyi (ROYAL SOC CHEMISTRY, 2013)
Cardiovascular disease (CVD) is a potent cause of mortality in both advanced and developing countries. While soluble CD40L (sCD40L) has been implicated as a correlative factor among CVD patients, methods to quantify sCD40L are not yet well-established. In this paper, we present an ability to separate and quantify sCD40L via a simple immunomagnetic assay. Composed of functionalized magnetic beads conferred with directionality and on-demand detachable quantum dots for subsequent optical analysis, our system utilizes the competitive nature of imidazole and nickel ions for histidine. In essence, we demonstrate the capacity to effectively separate and detect sCD40L within a clinically relevant range that contains the cut-off value for acute coronary disease. While sCD40L was used to conduct this study, we envision the use of our system for the separation and quantification of other biomarkers.
Keywords: ACUTE CORONARY SYNDROMES; SOLUBLE CD40 LIGAND; ENDOTHELIAL-CELLS; CRYSTAL-STRUCTURE; GLOBAL BURDEN; IN-VIVO; PART I; RISK; IMMUNOASSAYS; ATHEROSCLEROSIS